2018
DOI: 10.3390/toxins10120522
|View full text |Cite
|
Sign up to set email alerts
|

Loxosceles gaucho Spider Venom: An Untapped Source of Antimicrobial Agents

Abstract: The remarkable ability of microorganisms to develop resistance to conventional antibiotics is one of the biggest challenges that the pharmaceutical industry currently faces. Recent studies suggest that antimicrobial peptides discovered in spider venoms may be useful resources for the design of structurally new anti-infective agents effective against drug-resistant microorganisms. In this work, we found an anionic antibacterial peptide named U1-SCRTX-Lg1a in the venom of the spider Loxosceles gaucho. The peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 75 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…Eight two-fold serial dilutions of sarconesin II were evaluated at 100 µM final concentration and incubated for 1 h at 37 °C. Hemolytic activity was determined by measuring absorbance (Abs) at 405 nm and calculated as a percentage of 100% lysis control (0.1% Triton X-100); % hemolysis = (Abs sample–negative Abs)/(positive Abs − negative Abs) [137].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight two-fold serial dilutions of sarconesin II were evaluated at 100 µM final concentration and incubated for 1 h at 37 °C. Hemolytic activity was determined by measuring absorbance (Abs) at 405 nm and calculated as a percentage of 100% lysis control (0.1% Triton X-100); % hemolysis = (Abs sample–negative Abs)/(positive Abs − negative Abs) [137].…”
Section: Methodsmentioning
confidence: 99%
“…MS/MS peak list files were screened against a bank database constructed with the Lucilia proteins obtained from UNIPROT and NCBI [138,139] to determine their aa sequence. They were compared using PEAKS 8.5 (Bioinformatics Solutions Inc., Waterloo, ON, Canada) search software, using the following parameters: oxidation considered as variable modification, 10 ppm precursor mass tolerance and 0.6 fragment ion mass tolerance [137].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, an antimicrobial peptide (1695.75 Da), recently identified in L. gaucho venom, presented a remarkable similarity to specific regions of phospholipases D from Loxosceles genus. This peptide, referred to as U1-SCRTX-Lg1a, possesses an antibacterial effect on gram-negative bacteria [11]. The authors suggested that U1-SCRTX-Lg1a may have originated by limited proteolysis of a venom PLD.…”
Section: Molecular Characteristics Of Brown Spider Venomsmentioning
confidence: 99%
“…Antimicrobial peptides and proteins show a wide distribution and have been isolated from nearly all living organisms. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Beyond their antimicrobial effects, several AMPs have been shown to have other biological activities. 11,[22][23][24][25] One such protein group that represents the duplicity of activities for the same molecules is the tachykinin family.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides and proteins show a wide distribution and have been isolated from nearly all living organisms. 8 - 21 …”
Section: Introductionmentioning
confidence: 99%